Colorimetric Detection of Plasmodium vivax in Urine Using MSP10 Oligonucleotides and Gold Nanoparticles. - Yossef Alnasser; Cusi Ferradas; Taryn Clark; Maritza Calderon; Alejandro Gurbillon; Dionicia Gamboa; Uri S McKakpo; Isabella A Quakyi; Kwabena M Bosompem; David J Sullivan; Joseph M Vinetz; Robert H Gilman (PLoS Neglected Tropical Diseases)
Plasmodium vivax is the most prevalent cause of human malaria in the world and can lead to severe disease with high potential for relapse. Its genetic and geographic diversities make it challenging to control. P. vivax is understudied and to achieve control of malaria in endemic areas, a rapid, accurate, and simple diagnostic tool is necessary. In this pilot study, we found that a colorimetric system using AuNPs and MSP10 DNA detection in urine can provide fast, easy, and inexpensive identification of P. vivax. The test exhibited promising sensitivity (84%), high specificity (97%), and only mild cross-reactivity with P. falciparum (21%). It is simple to use, with a visible color change that negates the need for a spectrometer, making it suitable for use in austere conditions. Using urine eliminates the need for finger-prick, increasing both the safety profile and patient acceptance of this model.